Biomimicry levels as design inspiration in design - Othmani, Nurul Izzati; Mohd Yunos, Mohd Yazid; Ramlee, Noorliyana; Abdul Hamid, Nor Hamizah; Mohamed, Syahidah Amni; Lee, Bak Yeo (Human Resource Management Academic Research Society, 2022)
The relationship between design and nature has been intertwined for the past 400 years. Throughout history, designers have adopted nature to build shapes, forms, and ornamentation without understanding nature's behavior biomimicry. Nature's behavior biomimicry is a method that applies solutions to human problems by analyzing natural designs, processes, and systems. This innovative method refers to nature as an inspiration to solve design challenges. The method is the new science that studies nature as a model and inspiration to imitate the design and process of solving human problems. However, there is a lack of widespread and practical application of biomimicry as a design method; architecture commonly uses biology as a library of shapes, which is not biomimicry. Among the levels of biomimicry, the organism level is widely applied as a design tool to achieve a design solution. This paper reviews published research on the applications of biomimicry level, including its formative elements. Organism, behavior, and ecosystem level are mostly inspired or applied in the biomimicry concept. The content analysis was carried out to examine the published research articles on different perspectives of biomimicry and its application in design. The findings produce three levels of biomimicry that can serve as a regenerative design. There is a growing need for designs that work with nature to create a regenerative built environment, and designers can no longer ignore the relevance of bio-inspired theories and approaches to achieve a more sustainable future.